A study on the growth enhancement effects of chlorine on carbon nanotube forest in chloride-mediated chemical vapor deposition. (7th April 2021) - Hayashi, Tatsuhiro; Karita, Motoyuki; Nakano, Takayuki; Inoue, Yoku
Abstract: We investigated the growth enhancement effects of chlorine on carbon nanotube (CNT) grown by a chemical vapor deposition method in which FeCl2 is used as a catalyst precursor. Cross-sectional observation of the CNT forest revealed that the FeCl2 -originated catalyst showed a liquid-like behavior, and it caused metallic catalyst incorporation into the CNT. When chlorine gas flow was artificially added to the CNT synthesis process, the catalyst was further softened, and it increased the amount of metal filling in CNTs. This softening effect enhanced carbon absorption and diffusion at the catalyst and thus enabled the millimeter-long and high-density forest at a high temperature of 820 °C by suppressing the deactivation of the catalyst.